SYMBOLIC INTERACTIONISM IN MUSIC: ANALYSIS OF SOCIAL MEANING AND CULTURAL IDENTITY NEGOTIATION - Bondet Wrahatnala; Abraham Anton Febrindo Luwiga; Ifa Hanifa Rahman; Riana Kapri; Kristoforus Frederic Setyanto (Jurnal Kajian Seni, 2026)
This study examines musical practice as an arena of symbolic interaction in society, using the theoretical framework of symbolic interactionism. The framework stems from the assumption that social meaning is not inherently attached to objects or actions, but is formed through symbolic exchange between individuals and through processes of reflection and self-interpretation in social interaction. This research explores how music actors (players, listeners, communities) participate in the construction of musical meaning, how musical symbols are interpreted and negotiated, and how music functions as a medium for identity formation and social transformation. Through a descriptive-interpretive approach based on literature review of theories and previous research findings, it was found that symbolic interaction in musical practice encompasses processes of symbol repetition, public negotiation, role internalization, and intergenerational reinterpretation. Music becomes more than sound: it is a vehicle for symbolic communication that actively shapes and is shaped by society. These findings confirm that music analysis in ethnomusicology must consider aspects of symbolic micro-interaction in order to understand how cultural meaning, identity, and social structure are realized and transformed through music.